Basic Agricultural Public Expenditure Diagnostic Review : Republic of Cameroon, 2003-2012 - World Bank (Washington, DC, 2014)
This report summarizes the conclusions of a team of World Bank consultants who visited Cameroon from May 5 to 23, 2013, from July 28 to August 3, 2013, and from February 18 to 22, 2014 to lend support to the Ministry of Agriculture and Rural Development (MINADER), the Ministry of Livestock, Fisheries, and Animal Husbandry (MINEPIA), the Ministry of Forestry and Wildlife (MINFOF), and the Ministry of the Environment, Nature Protection and Sustainable Development (MINEPDED), in the preparation of a Basic Agricultural Public Expenditure Diagnostic Review. The Cameroon government assigns a crucial role to agriculture in stimulating growth, combating poverty, and job creation. The objectives of the Basic Agricultural Public Expenditure Diagnostic Review in Cameroon are as follows: a) to learn from past experience of budget implementation in the agricultural sector, identify bottlenecks, inefficiencies, and deviations from the stated goals, and recommend remedial measures for existing and future programs, with the intention of improving their impact and making them more efficient and equitable; b) to initiate the creation of databases and formulate the required methodology to conduct regular comparable reviews, thereby contributing towards the institutionalization of the process. This database should facilitate the analysis of factors affecting the growth of agriculture on a macroeconomic scale within the framework of a computable general equilibrium model soon to be established. This model will analyze the role of relative prices, public expenditure, and exchange rates on the growth in the sector; c) to assist the government in fostering an environment and management skills focused on results with special emphasis on improving planning, implementation, and budget analysis; and d) to improve awareness of the absorptive capacities of the sector by the government and its development partners to help decide how to increase the financial resources dedicated to agricultural development.